2023
DOI: 10.3390/molecules28010362
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from the Leaves of Ligustrum robustum and Their Bioactivities

Abstract: The leaves of Ligustrum robustum have been consumed as Ku-Ding-Cha for clearing heat and removing toxins, and they have been used as a folk medicine for curing hypertension, diabetes, and obesity in China. The phytochemical research on the leaves of L. robustum led to the isolation and identification of two new hexenol glycosides, two new butenol glycosides, and five new sugar esters, named ligurobustosides X (1a), X1 (1b), Y (2a), and Y1 (2b) and ligurobustates A (3a), B (3b), C (4b), D (5a), and E (5b), alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the previous phytochemical studies [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], about 90 chemical constituents, including trans - p -hydroxycinnamic acid, 34 trans - p -hydroxycinnamic acid esters ( Figure 1 ), flavonoid glycosides, lignan glycosides, and other compositions, were isolated and identified from the leaves of L. robustum .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous phytochemical studies [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], about 90 chemical constituents, including trans - p -hydroxycinnamic acid, 34 trans - p -hydroxycinnamic acid esters ( Figure 1 ), flavonoid glycosides, lignan glycosides, and other compositions, were isolated and identified from the leaves of L. robustum .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous biological investigations [ 14 , 15 , 16 , 17 ], the chemical compositions isolated from the leaves of L. robustum were tested, and the results showed that (1) trans - p -hydroxycinnamic acid displayed stronger α -glucosidase inhibitory activity than the positive control acarbose; (2) trans - p -hydroxycinnamic acid and several trans - p -hydroxycinnamic acid esters displayed no weaker fatty acid synthase (FAS) inhibitory activities than the positive control orlistat; (3) trans - p -hydroxycinnamic acid and a lot of trans - p -hydroxycinnamic acid esters revealed stronger 2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) ammonium salt (ABTS) radical scavenging effects than the positive control L-(+)-ascorbic acid and revealed moderate α-amylase inhibitory activities. What is more, trans - p -hydroxycinnamic acid esters might be hydrolyzed with catalysis of carboxylesterase or gastric acid in vivo [ 18 , 19 ] and release trans - p -hydroxycinnamic acid, meaning that trans - p -hydroxycinnamic acid esters are the prodrugs of trans - p -hydroxycinnamic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present anti-diabetic agents, including insulin, metformin, α-glucosidase inhibitors acarbose and N-substituted iminosugar C-glycoside [2], can deal with hyperglycemia, whereas their function to prevent the complications of diabetes is not ideal. Recent research [3] indicated that antioxidant natural ingredients with inhibitory actions on fatty acid synthase (FAS), α-glucosidase, and α-amylase might be a novel resource for preventing diabetes and its complications.…”
Section: Introductionmentioning
confidence: 99%
“…Ligustrum robustum (Roxb.) Blume, a shrub of the Oleaceae family, is widespread in Southwest China, Vietnam, Burma, Cambodia, and India [3]. The leaves of L. robustum, containing 3.96-3.99 mg•g −1 trans-p-hydroxycinnamic acid and 202.6-210.6 mg•g −1 total transp-hydroxycinnamic acid esters [4], have been not only used as a heat-clearing and detoxicating functional tea (Ku-Ding-Cha) but also consumed as a hypotensive, anti-diabetic, and weight-reducing folk medicine [3].…”
Section: Introductionmentioning
confidence: 99%